2013
DOI: 10.1038/ncomms3823
|View full text |Cite
|
Sign up to set email alerts
|

Fate tracing reveals hepatic stellate cells as dominant contributors to liver fibrosis independent of its aetiology

Abstract: Although organ fibrosis causes significant morbidity and mortality in chronic diseases, the lack of detailed knowledge about specific cellular contributors mediating fibrogenesis hampers the design of effective anti-fibrotic therapies. Different cellular sources including tissue-resident and bone marrow-derived fibroblasts, pericytes and epithelial cells have been suggested to give rise to myofibroblasts, but their relative contributions remain controversial, with profound differences between organs and differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

36
1,069
1
4

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 1,114 publications
(1,110 citation statements)
references
References 55 publications
(86 reference statements)
36
1,069
1
4
Order By: Relevance
“…Along these lines, an excellent very recent fate tracing study from the laboratory of Robert Schwabe, performed using a novel Cre-transgenic mouse that marks 99% of hepatic stellate cells, has shown that HSCs give rise to 82-96% of myofibroblasts in models of toxic, cholestatic and fatty liver disease [37]. This study unavoidably strongly suggests that any contribution by EMT to fibrogenesis should be considered as minor.…”
Section: Epithelial To Mesenchymal Transition (Emt) Process and Livermentioning
confidence: 87%
“…Along these lines, an excellent very recent fate tracing study from the laboratory of Robert Schwabe, performed using a novel Cre-transgenic mouse that marks 99% of hepatic stellate cells, has shown that HSCs give rise to 82-96% of myofibroblasts in models of toxic, cholestatic and fatty liver disease [37]. This study unavoidably strongly suggests that any contribution by EMT to fibrogenesis should be considered as minor.…”
Section: Epithelial To Mesenchymal Transition (Emt) Process and Livermentioning
confidence: 87%
“…This controversy can be attributed, at least in part, to the lack of specific markers to identify PFs to compare them directly with HSCs with respect to their contribution in collagen synthesis and deposition, both quantitatively and qualitatively. Previous studies identified PFs by negative selection, specifically the lack of vitamin A autofluorescence14 or of genetically labeled HSC markers 31. Because Thy1‐expressing mesenchymal cells represent PFs, gene expression changes of PF markers in normal and injured livers were assessed in Thy1 MC and HSC compartments and showed that specific expression of Thy1 and Fbln2 in Thy1 MCs and their absence in HSCs was maintained even after liver injury (Supporting Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The anatomic location of HSCs, which are in the space of Disse, and PFs, which are in the portal mesenchyme, seems compatible to the areas of injury in each experimental model. Nevertheless, the significance and the relative contribution of collagen synthesis and deposition by PFs compared to HSCs during liver injury remains largely controversial in that reports on HSC‐specific genetic labeling using Lrat‐driven or PDGFRβ‐driven Cre transgenic mice have suggested that HSCs contribute mainly to the pathogenesis of hepatic fibrosis, regardless of the etiologies 31, 32. This controversy can be attributed, at least in part, to the lack of specific markers to identify PFs to compare them directly with HSCs with respect to their contribution in collagen synthesis and deposition, both quantitatively and qualitatively.…”
Section: Discussionmentioning
confidence: 99%
“…As such, pericytes residing in different tissues have been termed according to their function and morphology, such as hepatic stellate cells in the liver and glomerular mesangial cells in the kidney (Lin et al, 2008;Mederacke et al, 2013). The morphology of pericytes can be stellate or spindle-like, with finger-like projections surrounding the vessels which are now believed to have a role in regulating blood flow (Hall et al, 2014) and inflammatory cell trafficking (Proebstl et al, 2012).…”
Section: Bone Marrow-derived Mesenchymal Stem Cells and Pericytes -Dementioning
confidence: 99%